Writing against extraction: Petroleum resistance in Sony Labou Tansi’s Je, soussigné cardiaque - Vessier, Ninon (Études littéraires africaines)

(untitled) (Association pour l'Étude des Littératures africaines (APELA), 2023)
This paper analyses the presence of petroleum in the 1977 play Je, soussigné cardiaque by Congolese writer Sony Labou Tansi. The play relates petroleum extraction led by the Spanish colonist Perono in the imaginary country of Lebango. The main character, Mallot, is a new teacher in town. He is accompanied by his pregnant wife and their young daughter. Mallot realizes that Perono rules over this petro-imperial tyranny, where the Lebangolese ecosystem is shaped and voided by resource exploitation. My reading focuses on the presence of petroleum beyond an anthropocentric perspective that sees it only as a resource, as I argue that petroleum offers new possibilities of nonhuman resistance to extraction.